การศึกษาสภาพและปัญหาการจัดการเรียนการสอนระดับก่อนประถมศึกษา ในโรงเรียนอนุบาลอำเภอ สังกัดสำนักงานคณะกรรมการการประถมศึกษาแห่งชาติ - เกรียงศักดิ์ เรืองศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purpose of this study was to study the state and problems of instructional organization at the preschool level in district kindergartens under the Office of the National Primary Education Commission. The samples were 500 subjects, which comprised of 250 administrators and 250 preschool teachers. Data collection methods were using questionnaires, interview and observation. The findings of this investigation were as follows: 1) The schools perceived the instructional organization policy from the Office of the National Primary Education Commission for the purpose of contributing standardization and quality of the schools education organization. 2) The surroundings were made arrangement to be attentive to learning activities in terms of learning atmosphere, cleanliness, safety and inherent equipped buildings. 3) Personnel preparation for the personnel organization and development was promoted. Administrators had considered experienced teachers to teach in preschool classes. The classroom teachers had chances to participate in academic seminars as well as educational observation tours concerning learning activities. 4) The preschool curriculum B.E. 2540 including its manual by the Academic Department were adapted suitable for the children and locally state. The parents were informed regarding the approaches and methodology of instruction and activities according to the curriculum. 5) Instructional well planned and activity preparation were appropriately set for the children of all different aged groups. The teachers planned for the activities in accordance with daily school schedules in order to develop the children in all areas in the extent to their happy learning. 6) Self-learning educational media, toys and natural materials were selected according to the children of all different aged groups. 7) It appeared that the children had experienced in actually learning activities. The teachers had paid attention to the children’s learning problems เท coordination with their parents. 8) Evaluation on the children s development was carefully made through observation and note-taking. 9) Under the supervision of the school administrators and their follow-up procedures, the teachers had been guided for the children s learning activities.